Analisis Wacana Gender Dalam Teks Satua Ni Bulan Kuning - Ida Bagus Gede Paramita (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The purpose of this study is to analyze the gender aspect in the text of Satua Ni Bulan Kuning. This text discusses women and their role in life. Against this background, the discourse about women emerged and became a struggle for feminists. Women are imaged as a symbol of prosperity, knowledge and strength. The method used in this research is qualitative research. The primary data in this research is the text of the Satua Ni Bulan Kuning, while the secondary data are books, scientific journals that support the analysis. The collected data is then selected to assist the analysis and the last step is drawing conclusions. The results of this study are able to reveal the hidden meaning in the Satua Ni Bulan Kuning. In fact, this unit does have a content of values that can enrich the repertoire of values for the development of the nation's character which has been widely echoed lately. Especially in satua Ni Bulan Kuning's research, the gender element contained in the Watugunung story is known and the meaning behind the symbols in the story is revealed.Keywords: Gender Discourse, Satua Text, Ni Bulan Kuning